Probleme of violence in international political conflicts of the present (International relations and international law Journal, 2016)
Violence has always played and continues to play a fundamental role in the big society. International relations are not left out of the phenomenon of violence, which is used today as the means to achieve political goals, as the various institutions within the state, and the various actors in world politics. There is a variety of ways in which the nationalist principle can be violated. The struggle for power, participation in the conflict, violence, security – are an essential attribute of world politics, which is known as a sphere is quite diverse, constantly updated and largely unpredictable. The article attempts to analyze the problems and prospects of violence as a phenomenon.Analysis and conclusions on the issue of violence, as well as responsibility for it have been applied in the present article.
Keywords: genocide; UN; USA; Rwanda; international politic conflict; youth andyouth movement